PENGARUH MEDIA PAPAN PINTAR TERHADAP KEMAMPUAN BERHITUNG ANAK DI TAMAN KANAK-KANAK AISYIYAH 14 AMPANG PADANG: Artikel - Nendes, Berlyan; Suryana, Dadan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the underdevelopment of children's numeracy skills, including their inability to sequence numbers, match numbers, and add them. The aim of this study was to determine the effect of using smartboards on children's numeracy skills at Aisyiyah Kindergarten 14 Ampang Padang. This study used a quantitative approach with a quasi-experimental method. The population consisted of 24 students, divided into two groups: B5 (experimental class) and B2 (control class) at Aisyiyah Kindergarten 14 Ampang. The data collection technique used questionnaires. The data were then processed using normality tests, homogeneity tests, and hypothesis testing using SPSS 26.0 for Windows. Based on the data analysis, the normality test showed that the data in the experimental and control classes were normally distributed. The homogeneity test showed that the data were homogeneous. The hypothesis test using a paired sample t-test yielded a sig (2-tailed) of 0.000 < 0.05. Thus, it can be concluded that there is a significant (real) influence between the learning carried out by researchers in the experimental class with smart board media to improve children's counting skills at Aisyiyah Kindergarten 14 Ampang Padang.